Effects of mergers and galaxy interactions at intermediate densities in the SDSS-DR4 - Perez, J. (2009)
Recently, several observational works have provided evidence in favor of a pre-processing of galaxies at moderate environments. These evidences show that the transition of galaxies onto the red-sequence could take place in galaxy groups in the outskirt of clusters or in the infalling populations. Based on the evidence that interacting and merging systems are priviledged found at intermediate densities, we use the SDSSDR4 data to analyse the role of mergers and close galaxy interactions as environmental processes to lead to evolutionary transformations. We explore the properties of galaxy pairs and merging systems at different local and global density environments, comparing them with those of isolated galaxies in an unbiased control sample.